Meiotic and mitotic behaviour of B chromosomes of ryegrass. - TECHIO, V. H. (2010)
ABSTRACT - Mitotic and meiotic analyses using conventional and fluorescent stains were employed in plants (accession ETBAZ 055 - origin: Capão do Leão, Rio Grande do Sul State, Brazil) from the Germplasm Active Bank of Ryegrass (Banco Ativo de Germoplasma de Azevém) of Embrapa, for observing the behaviour of B chromosomes. In several meiotic stages, there were observed up to two B chromosomes, which have presented an unstable behaviour regarding their precocious ascension to metaphase I or delays during anaphase I. At the end of the process, the Bs showed predominantly segregation for the nuclei under formation in order to guarantee their propagation. Concerning the cells that comprise the anther tapetum and the root meristems, the B chromosomes have presented a more stable behaviour. RESUMO - Análises mitóticas e meióticas com coloração convencional e fluorescente foram realizadas em plantas (acesso ETBAZ 055 - procedência Capão do Leão, Rio Grande do Sul) provenientes do Banco Ativo de Germoplasma de Azevém da Embrapa para observar o comportamento dos cromossomos B. Em vários estágios da meiose, foram observados um a dois cromossomos B, os quais apresentaram um comportamento instável, com ascensão precoce na metáfase I ou atrasos na anáfase I. Ao final do processo, os Bs exibiram predominantemente segregação para os núcleos em formação, a fim de garantir a sua propagação. Nas células que constituem o tapete da antera e nos meristemas da raiz, os cromossomos B apresentaram um comportamento mais estável.